Using technical assistance to bridge the gap between policy, research, and implementation - Ealy, Phillip L.; Tyler-Mackey, Crystal; Ashurst, Kerri; Blue-Terry, Misty; Cano-Guin, Autumn; Dierenfield, Candi; Grant, Samantha; Harmon, Denae; Payne, Pamela B.; Wells-Marshall, Jennifer; Perkins, Daniel F. (Frontiers in Public Health, 2024)
This case study on the Children, Youth, and Families At-Risk (CYFAR) Professional Development and Technical Assistance (PDTA) Center highlights a government-funded entity's efforts to provide technical assistance to federal grantees of the CYFAR Sustainable Community Projects (SCP) grant program. The PDTA Center aligns with and supports components of an evidence-based system for innovation support. Through these components, the system provides targeted tools, training for CYFAR SCP grantees, dedicated technical assistance in the form of coaching, and quality improvement support through the evaluation of available program data.